Marketing Alliances Between Retailers and Manufacturers of Consumer Durable Goods - Marzanna K. Witek-Hajduk (Gospodarka Narodowa. The Polish Journal of Economics, 2017)
The aim of this article is to analyze marketing alliances between producers and retailers. In our view, there is a lack of research and publications on this increasingly important subject. This paper seeks to provide answers to the following research questions: (i) What is the scope of marketing alliances between producers and retailers on the market for consumer durable goods? (ii) What are the reasons for creating specific marketing alliances between production companies and retail firms trading in consumer durable goods? In order to answer these questions, qualitative research has been conducted. It took the form of interviews with managers of production and retail companies operating on the Polish market for consumer durable goods. The research led us to conclude that cooperation between production companies and retailers on the Polish market for consumer durable goods often extends beyond standard vertical relations within the distribution system. We have also concluded that such alliances include cooperation in various marketing activities. The most important reason for creating such marketing alliances is a desire to limit business risk. This is possible due to an exchange of information between both partners in marketing alliances. Another important reason for such alliances is cooperation in shaping the product range, which helps reduce business risk and increase revenue.